Exploring the Use of X (Formerly Twitter) in Students’ English Writing Skills: Basis for the Development of Instructional Material - Roxas, Millet Joy; Nama, Viernalyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of X (formerly Twitter) on the English writing skills of Bachelor of Secondary Education Major in English students and served as the basis for the development of an English Writing Enhancement Toolkit. Anchored on Connectivism Theory, the study employed a convergent mixed-method research design involving 30 purposively selected students with active X accounts from a university in Quezon City during the School Year 2025–2026. Quantitative data were collected using a researcher-made survey questionnaire, while qualitative data were gathered through semi-structured interviews. Descriptive statistics, including weighted mean and standard deviation, were used to analyze quantitative data, whereas thematic analysis was employed for qualitative responses. The findings revealed that respondents generally perceived X as a beneficial platform for learning, particularly in terms of diversity of knowledge sources, learning as connection-making, distributed knowledge systems, and capacity to learn. Personal learning growth emerged as the primary purpose for using the platform, while academic improvement, collaboration and networking, and staying updated received lower ratings. Qualitative findings identified several challenges in English writing, including limited expression due to character constraints, grammar and vocabulary difficulties, fear of misinterpretation and social judgment, self-censorship, time pressure, and the influence of informal writing habits. The integrated findings indicated that X serves as a useful supplementary platform for language exposure, communication, and writing practice but remains limited as a formal academic writing environment. Based on the results, an English Writing Enhancement Toolkit was developed to address identified writing challenges and support English writing development. The study aligns with SDG 4 (Quality Education) and SDG 9 (Industry, Innovation and Infrastructure) by exploring the educational use of digital technologies to support language learning. Its sustainability contribution lies in promoting educational and digital sustainability through the responsible integration of social media into English language instruction and literacy development.
Keywords: Connectivism Theory; Digital Literacy; English Writing Skills; Personal Learning Growth; Social Media; X (Twitter); Writing Enhancement Toolkit